2011
DOI: 10.1182/blood.v118.21.305.305
|View full text |Cite
|
Sign up to set email alerts
|

BT062, An Antibody-Drug Conjugate Directed Against CD138, Shows Clinical Activity in Patients with Relapsed or Relapsed/Refractory Multiple Myeloma

Abstract: 305 Background: CD138 (Syndecan-1) is highly overexpressed in various solid tumors and hematological malignancies and represents one of the most specific target antigens for identification of multiple myeloma (MM) cells. BT062 (Biotest AG Dreieich, Germany) is an antibody-drug conjugate, comprised of the anti-CD138 chimerized MAb (nBT062) and the cytotoxic agent DM4. Once bound to CD138 on a target cell, the conjugate is internalized and releases DM4, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“… 17 , 18 XBP1 (X-box binding protein 1), CD138 (Syndecan-1) and CS1 (CD2 subset 1, CRACC, SLAMF7, CD319) antigens are highly expressed on MM with therapeutic potential, as demonstrated in preclinical and clinical studies. 19 - 24 In previous studies, we identified immunogenic HLA-A2-specific peptides derived from each of these target antigens including heteroclitic XBP1 unspliced (US) 184-192 (YISPWILAV), 25 heteroclitic XBP1 spliced (SP) 367-375 (YLFPQLISV), 25 native CD138 260-268 (GLVGLIFAV) 26 , and native CS1 239-247 (SLFVLGLFL) 27 peptides. These selected immunogenic peptides, either individually or combined as a four-peptide cocktail, induced antigen-specific CTL with functional activities against HLA-A2 + MM cells.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 XBP1 (X-box binding protein 1), CD138 (Syndecan-1) and CS1 (CD2 subset 1, CRACC, SLAMF7, CD319) antigens are highly expressed on MM with therapeutic potential, as demonstrated in preclinical and clinical studies. 19 - 24 In previous studies, we identified immunogenic HLA-A2-specific peptides derived from each of these target antigens including heteroclitic XBP1 unspliced (US) 184-192 (YISPWILAV), 25 heteroclitic XBP1 spliced (SP) 367-375 (YLFPQLISV), 25 native CD138 260-268 (GLVGLIFAV) 26 , and native CS1 239-247 (SLFVLGLFL) 27 peptides. These selected immunogenic peptides, either individually or combined as a four-peptide cocktail, induced antigen-specific CTL with functional activities against HLA-A2 + MM cells.…”
Section: Introductionmentioning
confidence: 99%
“…CD138 antibody (BT062, indatuximab) was used in the treatment of patients with MM. In a phase I/II clinical trial of BT062, a clinical response was reported in only 1 out of 23 patients [101]. The combination of BT062 with lenalidomide increased the overall response rate by up to 83% [102].…”
Section: Cd138mentioning
confidence: 99%
“…CD138's elevated expression on MM cells and its active role in the disease phenotype make it a promising MM BsAb target. Additionally, mCD138's role in preventing apoptosis likely makes tumor cells addicted to this molecule, although a significant proportion of patients were shown to have CD138-negative MM clones (141,147). Potential drawbacks of CD138 include its high expression on epithelial cells and the accumulation of sCD138 in the BM.…”
Section: Cd138 (Syndecan-1)mentioning
confidence: 99%